Clinical Case: Atypical Warfarin-induced Skin Necrosis - T. V. Kondratieva; L. V. Popova; S. S. Karachev; A. S. Lishuta; M. Z. Kanevskaya (Рациональная фармакотерапия в кардиологии)
Warfarin-induced skin necrosis (WISN) is a rare complication of antivitamin K therapy, which occurs in 0.01-0.1% of cases and develops during the first 10 days of the therapy start in the fat-rich tissues. In the literature, there is the increasing number of descriptions of case reports of the so-called atypical WISN, which develops much later – in months and even years from the therapy start – on the other parts of the body, mainly on the extremities. Conceivably there are several risk factors for the WISN development: a noncompliance of the antivitamin K regiment intake or the repeated therapy, a liver dysfunction or drug interactions, but a clear relationship has not been established yet as there have been only several hundred cases of WISN registered worldwide. One of the risk factors for WISN is congenital thrombophilia. The case presented demonstrates the development of an atypical WISN, which developed after 2 months from the start of the treatment with warfarin in a patient who is a carrier of mutation factor V Leiden. A resolution of the symptoms occurred as a result of treatment with unfractioned heparin.